A Brother for Thutmose III (Cairo Museum BN 104)*. Issue 1 (January 2013) - Metawi, Dina
Publication of a dyad (Cairo Museum BN 104) representing Nebnefer, 'a w'b-'ḳ priest of Amun in Henket-ankh', and his wife. Stylistically the dyad is probably datable to the reign of Thutmose III, and it also bears his cartouche. Nebnefer's filiation formula refers to him as born of the 'royal mother', possibly making him a hitherto unknown brother of Thutmose III. If so, the dyad provides a previously unattested title for Queen Isis, the mother of Thutmose III: wrt ḫnr '3t (n) 'Imn. Notwithstanding Nebnefer's titular association with Henket-ankh, Greek graffiti scratched on the statue base, published here for the first time, argue for a different provenance for the dyad.